The Novel Role of Healing from Bacterial Infections of Lower Limb Open Fractures by X-Ray Exposure - Ali A. Mahdi; Tuqa S. Al-Salmani; Mustafa M. Al-Qaisi (International Journal of Microbiology)
Introduction. An open fracture refers to a break in the skin, which is exposed to microbial contamination and eventually leads to most complicated infections. X-rays can kill bacteria by causing irreversible DNA damage. Objective. To confirm the role of X-ray exposure in treating infected wound fractures at the lower limb and determine X-ray exposure times. Methods. Fifty-one wound swabs were collected from patients with infected open fractures at the lower limb with grade II, IIIA, B, and C according to the Gustilo and Anderson classification system and then cultured. The bacterial isolates were identified by biochemical tests and the VITEK-2 System and tested against several antibiotics. The X-ray exposure was done for open fractures by radiography (at kV133 and 5 milliambers). Results. The higher isolation rate was recorded for Staphylococcus aureus with 21 (41.2%) isolates, and most of them (20, 95.2%) were isolated from grade II fractures. The isolation rate of Gram-negative bacteria was 25.5% for Escherichia coli with 13 isolates, 19.6% for Pseudomonas aeruginosa with 10 isolates, and 13.7% for Klebsiella pneumoniae with 7 isolates, most of which were isolated from grade III fractures. The isolation rate of P. aeruginosa was 60% (6 isolates) from grade IIIA and 71.4% (5 isolates) from grade IIIB for K. pneumoniae, while for E. coli it was 69.2% (9 isolates) from grade IIIC. All the bacterial isolates recorded high levels of antibiotic resistance against most tested antibiotics. Wound cultures of grade II fractures appeared sterile after the first X-ray exposure, and these wounds were infected with S. aureus or P. aeruginosa. However, cultures of grade IIIA and IIIB fractures appeared sterile after the second X-ray exposure for all isolated bacteria, except for S. aureus (grade IIIA fractures) (after the third X-ray exposure). Grade IIIC fractures showed sterile culture after the third X-ray exposure for wounds infected with P. aeruginosa and E. coli. Conclusions. The study concluded that X-ray exposure showed high effectiveness in treating infected open fractures.